Balinese Traditional Medicine under the Bali Governor Regulation No. 55/2019: Policy Implementation, Utilization Gaps, and Future Integration - I Wayan Wiasthana Ika Putra; Sofjan Aripin; Bambang Supriyono; I Made Damriyasa (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
This study evaluates the implementation of Bali Governor Regulation No. 55/2019 on Balinese Traditional Medicine (BTM) across traditional healers (pengusada), community health centers (Puskesmas), and hospitals. A quantitative descriptive survey was conducted in 2023 using structured online questionnaires distributed to 64 pengusada, 111 Puskesmas leaders, and 38 hospital directors. Data were analyzed using descriptive statistics. The regulation strengthened pengusada legitimacy, with 70% reporting improved recognition. While 91% of Puskesmas have integrated BTM services, hospital utilization remains low, with 70.6% reporting fewer than ten monthly visits. Key barriers include shortages of certified personnel, limited funding, weak infrastructure, and exclusion from National Health Insurance (BPJS) coverage. Nevertheless, 98.2% of facility leaders support integration with conventional healthcare and wellness tourism. Strengthening certification, financing mechanisms, and reimbursement inclusion is essential for sustainable integration within Bali’s healthcare system